2017
DOI: 10.1002/poc.3748
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphorous ligands in hydrogenase‐inspired iron‐based catalysts: A DFT study on the energetics of metal protonation as a function of P‐atom substitution

Abstract: The present paper reports a study on the energetics of protonation of a hydrogenase biomimetic complex, [Fe 2 (μ-adt)(CO) 4 (PMe 3 ) 2 ] (adt = Nbenzylazadithiolate), and of its homologue featuring triphenylphosphine ligands in place of trimethylphosphines. Formation of a terminal hydride on one of the Fe centres was considered first, given the key relevance of terminal hydride species in the enzymatic mechanism. Theoretical calculations highlight that, in a vacuum, terminal protonation of the selected Fe ion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
(52 reference statements)
1
5
0
Order By: Relevance
“…Deviations of atomic charges turned out to be small (maximum deviation 0.03 e both for the oxo and the sulfide species). Such picture is analogous to what was found in the above-mentioned study on [FeFe]-hydrogenase biomimetic models 11 whose atomic charges varied only slightly as a function of the presence of phosphine ligands of different size and nature (PCH 3 , PPh 3 ).…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Deviations of atomic charges turned out to be small (maximum deviation 0.03 e both for the oxo and the sulfide species). Such picture is analogous to what was found in the above-mentioned study on [FeFe]-hydrogenase biomimetic models 11 whose atomic charges varied only slightly as a function of the presence of phosphine ligands of different size and nature (PCH 3 , PPh 3 ).…”
Section: Resultssupporting
confidence: 86%
“…The design of new metalorganic complexes for catalytic purposes requires careful consideration of electronic and steric effects in order to tune the activity of such species. In a previous theoretical study of organometallic diiron catalysts for proton reduction, 11 we showed that protonation of Fe ions in complexes bearing bulky and strongly electron-donating PPh 3 ligands is highly favoured compared to the analogous reaction involving the PMe 3containing species when studied in a vacuum. However, the trend inverted when the models instead are studied in a continuum solvent.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Such a study mainly regards the hydrogenase activity of the enzyme and includes a comparative analysis of the binding reactions of the physiologic substrate—i.e., CO—and of dihydrogen to the Cu ion. Similarly to previous studies on H 2 - and CO-binding enzyme models in which a pure functional was used in conjuction with triple-zeta bases (Greco et al, 2015; Rovaletti and Greco, 2018), geometry optimizations and energy calculations were carried out in vacuo at BP86/def2-TZVP level (Perdew, 1986; Becke, 1988; Weigend and Ahlrichs, 2005). As far as the energetics of CO binding is concerned, the computed ΔE was as negative as −64 kJ/mol.…”
Section: Small- and Medium-sized Qm-cluster Modelsmentioning
confidence: 99%